The effect of psychological contract violation, work-life balance, and career development on employee performance mediated by job satisfaction - Shinta Oktafien; Anton Budi Santoso; Wan Amira Wan Ahmad (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study was conducted to analyze the factors influencing employee performance, mediated by job satisfaction, among permanent lecturers at accredited private universities in Bandung City. This research falls under verification research, aiming to test the validity of a hypothesis designed through field data collection. The data processing and analysis techniques employed in this study included descriptive statistical tests and structural equation model (SEM) tests. The population for this study comprised all permanent lecturers at accredited private universities in Bandung City, totaling 1,009 individuals, with a sample size of 286. The sampling technique utilized in this study was cluster sampling. The results indicate that psychological contract violation, work-life balance, and career development, both directly and indirectly through job satisfaction as the mediating variable, affect employee performance. However, not all formulated hypotheses yield acceptable results.